Resistance exercise: an effective strategy to reverse muscle wasting in hemodialysis patients?. Issue 3 (28th August 2014) - Rhee, Connie M.; Kalantar-Zadeh, Kamyar
Abstract : Muscle wasting is a common complication afflicting maintenance hemodialysis (HD) patients, and it is associated with decreased muscle function, exercise performance, physical function, and quality of life. Meanwhile, numerous epidemiologic studies have consistently shown that greater muscle mass (ascertained by body anthropometry surrogates, body composition tests such as dual x‐ray absorptiometry, and/or serum creatinine in patients with little to no residual kidney function) is associated with increased survival in this population. The pathophysiology of muscle wasting in HD patients is complex and may be caused by poor dietary intake, catabolic effects of dialysis therapy, hormonal alterations (e.g., decreased levels or resistance to anabolic hormones, increased levels of catabolic hormones), inflammation, metabolic acidosis, and concurrent comorbidities. Muscle disuse resulting from low physical activity is an important yet under‐appreciated risk factor for muscle wasting. Intra‐dialytic resistance exercise training has been suggested as a potential strategy to correct and/or prevent this complication in HD patients, but prior studies examining this exercise modality as an anabolic intervention have shown mixed results. In a recently published 12‐week randomized controlled trial of a novel intra‐dialytic progressive resistance exercise training (PRET) program vs. control therapy conducted in HD and non‐HD patients, PRET resulted in increased muscle volume and strength in both groups. At this time, further study is needed to determine if anabolic improvements imparted by resistance exercise translates into improved physical function and quality of life, decreased hospitalization and mortality risk, and greater cost‐effectiveness in HD patients.